Minirefleksje nad maksikwestiami, czyli o aksjologicznych aspektach praworządności - Szadok-Bratuń, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The first part of the draft aims at presenting the law and order as a philosophical construct with regard to dichotomous divisions. The scope of the discourse has been reduced to two planes, also referred to as problems. The first, understanding the designations of opposition of such terms as eunomy — isonomy. The second, selective presentation of the opposing types of the law and order in the key of conceptual correlation: the law and order — legality, the subjective law and order — the objective law and order, the formal law and order — the material law and order.The second part of the study is an attempt to understand the law and order in the optics of the axiological and legal binomial. Analogically to the first part of the publication, the methodological symmetry was maintained. The analyzes were made in two cognitive areas. The first is the definition of the material law and order understood in an inclusive way, including the attributes of the law and order. The second one is an attempt to select the principles-values from which the epicurean therapeutical tetrapharmacon should be composed in relation to the law and order.
Keywords: axiology of law; law and order; dignity; freedom; equality; justice; value